Evaluation of High School Students' Perceptions and Views on Distance Education During COVID-19 Pandemic - Çelik, Öykü (Open Schools Journal for Open Science, 2022)
The COVID-19 disease, which spread all over the world and caused a pandemic, disrupted education the most. Countries had to quickly switch to the distance education model in schools and universities in order to prevent the spread of the epidemic. In our study, in which we evaluated the perceptions and views of high school students about distance education, almost two-thirds of the students stated that distance education is not an adequate and effective learning model. Despite the fact that today is the age of technology, students' reporting that a more effective learning will be achieved with face-to-face education shows that the distance education model should be developed and improved.